Sustainable use of waste plastic modifiers to strengthen the adhesion properties of asphalt mixtures. (28th February 2020) - Haider, Safeer; Hafeez, Imran; Jamal,; Ullah, Rafi
Highlights: Moisture damage resistance of waste plastic modified asphalt mixtures was conducted. Wet method of mixing was found relatively better than dry method of mixing to resist moisture damage in asphalt mixtures. Calcium carbonate and dolomite type aggregate quarries were found relatively better against moisture resistance due to high polarity, basic and hydrophobic nature of aggregate. Waste plastic modifiers in asphalt pavement extends pavement service life as well as reduction of raw material to maintain sustainable environment. Abstract: Low pavement performance increases environmental degradation and reduces natural reserves. This reduction in pavement's service life is attributed towards moisture susceptibility, rutting and fatigue failures of asphalt pavements. To overcome this, waste plastic modifiers were used in this research study to improve the asphalt mixtures moisture damage resistance and hence the asphalt pavement's service life. Four different sources of aggregate based on petrography of rock were selected to ascertain the effect of different minerals on moisture damage. Qualitative as well as quantitative tests were utilized to assess moisture sensitivity. The analysis of test data showed that high density polyethylene and wet method of mixing has relatively better adhesion properties. Moreover, acidic aggregates containing granite minerals showed more loss of adhesion than basic aggregate quarries due their less polarity and hydrophilic nature. Modified Lottman as well as Hamburg wheel track test were found relatively better for compacted asphalt mixture than Marshall stability test for moisture damage assessment. This study recommends using waste plastics in the asphalt mixtures to improve performance life of the pavement and reduces the environmental degradation.